Pemberdayaan Masyarakat Nagari Siaga Bencana Banjir Di Nagari Pangkalan Kecamatan Pangkalan Kabupaten Limapuluhkota - Syafri Anwar; Khairani Khairani; Dilla Angraina (Universitas Prof. Dr. Hazairin, S.H, 2017)
This devotion aims to make Nagari Nagari Pangkalan District Pangkalan District Limapuluhkota, become Nagari Disaster Alert, so that the Nagari Pangkalan tough and standby if sudden floods occur and the impact is not too big. The low knowledge and awareness of the flood and environmental awareness caused by the priority of the economic interests, so that many people do land clearing, including around the Maek River. Yet with the opening of land that is not balanced with environmental conditions, then there is rain with a great intensity, then the area becomes an area prone to flood disaster. This proved two consecutive years (2016 and 2017) floods that exceed 1 meter so that the impact on all facilities and infrastructure including agriculture and plantations owned by Nagari Pangkalan community. Therefore, the community service team has conducted workshops and counseling to representatives from various levels of society, so as to increase the knowledge and spirit of the community to make their Nagari Disaster Alert. The next plan of the devotion team will be to carry out the Focus Group Discussion to discuss the findings and findings of the workshop and counseling.